A pre‐systematic review on the use of masks as a protection material for SARS‐COV‐2 during the COVID‐19 pandemic. Issue 9 (27th April 2021) - Pires, Carla
Abstract: Background: Coronavirus disease 2019 (COVID‐19) was first reported in Wuhan, China on 31 December 2019. Aims: to review, analyse and discuss all works about the wearing and development of facemasks as potential protection against SARS‐COV‐2 during the COVID‐19 pandemic. Methods: PubMed, SciELO, Google Scholar and DOAJ were browsed. Keywords: "mask and (SARS or Cov)" (1 August 2019 to 12 April 2020). Inclusion criteria: original research. PRISMA criteria were followed. Results: Twenty‐one works were selected. Identified topics: effectiveness of protective equipment/devices (PE) (n = 3), universal wearing of facemasks plus other protective measures in the community (n = 3), impact of infection control measures on hospitals and epidemiological tracing (n = 3), development of new PE (n = 2), sanitisation of facemasks (n = 4), clinical guidance (n = 4) and questionnaires (n = 2). Discussion: It seems that the effectiveness of PE, namely facemasks, is not fully known. Universal wearing of facemasks may be simultaneously recommended with other protective measures. Nosocomial and community infections seem to be preventable. New PE, methods of facemask sanitisation and clinical guidance are emerging, but caution is recommended regarding their adoption, revision and monitoring by international boards and institutions. Questionnaires are useful tools for collecting citizens' opinions on implementing public health measures, and thus contribute to mitigating the COVID‐19 pandemic. Conclusions: Universal wearing of facemasks in the community is likely to be recommended during the COVID‐19pandemic. Since SARS‐COV‐2 is highly contagious, a set of measures should be considered. Facemask sanitisation is possible, but standardised procedures are lacking. New PE is emerging and requires detailed regulatory approval. It is advisable to monitor public opinion.